Project Report on Remote Installer - A SANGILI SUBRAMANIAN, TAUQEER AHMED and A KISHORE TARIQ (1999)
INTERNAL GUIDE: K K MATHEWS, MVJCE EXTERNAL GUIDE: NOORIE KHAN, MONOR TECHNOLOGIES
Keywords: Remote Installer